2021
DOI: 10.1007/s13202-021-01316-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of palm oil additives on the pour point and wax deposition tendencies of Chenor crude oil

Abstract: One of the major concerns during the production of crude oil especially in tropical waters is the deposition of wax on to the walls of the pipeline. This is due to the low seabed temperatures which can be below the wax appearance temperature (WAT) which leads to wax depositing out through molecular diffusion. Currently, there are many methods to prevent and remedy wax deposition but most of these solutions pose a serious environmental threat and are expensive to produce. Hence, this research investigated the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Pour point depressants function by adhering to the wax crystals’ surface. The consequent surface layer of the pour point depressants stops wax crystals from growing, preventing them from absorbing oil and gelling. , The observed pour point temperatures of 0.25% PE + 1% MNPs, 0.25% PE + 2% MNPs, and 0.5% PE + 2% MNPs of heavy (B) crude oil and 0.25% PE + 2% MNPs, and 0.5% PE + 2% MNPs of light (A) crude oil samples were less than −36 °C. In contrast, the pour points of blank samples are +6 °C and + 27 °C for light and heavy crude oils, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pour point depressants function by adhering to the wax crystals’ surface. The consequent surface layer of the pour point depressants stops wax crystals from growing, preventing them from absorbing oil and gelling. , The observed pour point temperatures of 0.25% PE + 1% MNPs, 0.25% PE + 2% MNPs, and 0.5% PE + 2% MNPs of heavy (B) crude oil and 0.25% PE + 2% MNPs, and 0.5% PE + 2% MNPs of light (A) crude oil samples were less than −36 °C. In contrast, the pour points of blank samples are +6 °C and + 27 °C for light and heavy crude oils, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…141 Azeem et al 142 combined olive oil with pentadecane and VA to generate a composite polymer, which inhibited wax deposition through a cocrystallization mechanism, and lowered the pour point by 8 °C at 1000 ppm. Ragunathan et al 143 studied the inhibitory effect of palm oil compared with that of the commercial PPD ethylene-vinyl acetate (EVA) and reported that there was a critical concentration at which PPD decreased the pour point of crude oil. When the PPD exceeded the critical concentration, it aggregated and crystallized, increasing the pour point of crude oil.…”
Section: Green Pour Pointmentioning
confidence: 99%
“…To measure the wax deposition IE, a cold finger setup (CF) was used to simulate the wax deposition qualitatively in the field by applying a certain shear rate and temperature gradient of a waxy fluid. [19,[46][47][48][49] The CF setup apparatus is popular to use for wax deposition assessment because it is small in size, low in cost, less material intensive, and easy to operate. [46][47][48][49] Our used CF setup consists of a cylindrical glass finger with an outside diameter of 40 mm that is placed inside a cylindrical sampling vessel with a diameter of 99 mm, hot water sink, and water chiller (Figure 2).…”
Section: Cf Analysismentioning
confidence: 99%
“…[19,[46][47][48][49] The CF setup apparatus is popular to use for wax deposition assessment because it is small in size, low in cost, less material intensive, and easy to operate. [46][47][48][49] Our used CF setup consists of a cylindrical glass finger with an outside diameter of 40 mm that is placed inside a cylindrical sampling vessel with a diameter of 99 mm, hot water sink, and water chiller (Figure 2). The cylindrical glass finger is composed of a glass vacuum trap device that operates by internally circulating cold water (at 5 C) using the water chiller.…”
Section: Cf Analysismentioning
confidence: 99%